PROTECTION OF COPYRIGHT IN THE DIGITAL AGE: CHALLENGES AND SOLUTIONS IN VIRTUAL SPACE (World Bulletin of Management and Law, 2025)
In the digital age, copyright protection faces numerous challenges due to the widespread availability and ease of content distribution in virtual spaces. This article explores the key issues, such as unauthorized distribution, digital piracy, the lack of international legal standardization, and the difficulty of identifying copyright violators. Additionally, it examines innovative solutions, including strengthened legal frameworks, digital rights management (DRM), blockchain technology, artificial intelligence for enforcement, and increased public awareness. By addressing these challenges through a combination of legal, technological, and collaborative efforts, this study highlights the importance of a comprehensive and adaptive approach to copyright protection in the evolving digital landscape.
Keywords: Copyright protection; digital rights management; intellectual property